Bismuth(iii) triflate as a novel and efficient activator for glycosyl halides. Issue 14 (24th March 2021) - Steber, Hayley B.; Singh, Yashapal; Demchenko, Alexei V.
Abstract : Presented herein is the discovery that bismuth(iii ) trifluoromethanesulfonate (Bi(OTf)3 ) is an effective catalyst for the activation of glycosyl bromides and glycosyl chlorides. Abstract : Presented herein is the discovery that bismuth(iii ) trifluoromethanesulfonate (Bi(OTf)3 ) is an effective catalyst for the activation of glycosyl bromides and glycosyl chlorides. The key objective for the development of this methodology is to employ only one promoter in the lowest possible amount and to avoid using any additive/co-catalyst/acid scavenger except molecular sieves. Bi(OTf)3 works well in promoting the glycosidation of differentially protected glucosyl, galactosyl, and mannosyl halides with many classes of glycosyl acceptors. Most reactions complete within 1 h in the presence of only 35% of green and light-stable Bi(OTf)3 catalyst.